Adaptive leadership during challenging times: Effective strategies for health professions educators: AMEE Guide No. 148. (1st February 2023) - McKimm, Judy; Ramani, Subha; Forrest, Kirsty; Bishop, Jo; Findyartini, Ardi; Mills, Chloe; Hassanien, Mohammed; Al-Hayani, Abdulmonem; Jones, Paul; Nadarajah, Vishna Devi; Radu, Greg
Abstract: Leadership and management are becoming increasingly recognised as vital for high-performing organisations and teams in health professions education. It is often difficult for those embarking on leadership activities (as well as more experienced leaders) to find their way through the volume of literature and generic information on the topic. This guide aims to provide a framework for developing educators' understanding of leadership, management, and followership in the context of health professions education. It explains many relevant approaches to leadership and suggests various strategies through which educators can develop their practice to become more effective.